2018
DOI: 10.1007/s00425-018-2912-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and tolerance mechanisms of seed cracking under low temperatures in soybean (Glycine max)

Abstract: In soybean, occurrence of, or tolerance to, seed cracking under low temperatures may be related to the presence or absence, respectively, of proanthocyanidin accumulation in the seed coat dorsal region. Soybean seeds sometimes undergo cracking during low temperatures in summer. In this study, we focused on the occurrence and tolerance mechanisms of low-temperature-induced seed cracking in the sensitive yellow soybean cultivar Yukihomare and the tolerant yellow soybean breeding line Toiku 248. Yukihomare exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Studies have shown that seed coat tear/crack may be related to the physical fatigue of the tissues in the final stage of maturation due to the changings of humidity and temperature of hot environments, which is typical of the tropical region of Brazil (Ma et al, 2004;Qutob et al, 2008;Forti et al, 2010;Senda et al, 2018). The tetrazolium test on soybean seeds in this study showed that the samples with coat tear/crack were progressively affected by moisture.…”
Section: Effect Of the Seed Coat Tear On Moisture Damage And Physiolomentioning
confidence: 51%
See 1 more Smart Citation
“…Studies have shown that seed coat tear/crack may be related to the physical fatigue of the tissues in the final stage of maturation due to the changings of humidity and temperature of hot environments, which is typical of the tropical region of Brazil (Ma et al, 2004;Qutob et al, 2008;Forti et al, 2010;Senda et al, 2018). The tetrazolium test on soybean seeds in this study showed that the samples with coat tear/crack were progressively affected by moisture.…”
Section: Effect Of the Seed Coat Tear On Moisture Damage And Physiolomentioning
confidence: 51%
“…The coat tear/crack on soybean seed is defined as a physiological seed defect, verified in the reproductive phase R6. The tearing can be explained by seed coat crack on the dorsal side provoked by the rapid turgidity of the seed cells in function of the excess of water (Qutob et al, 2008;Senda et al, 2018). The tear is aggregated from moisture, but it does not arise from it.…”
Section: Introductionmentioning
confidence: 99%
“…The Ic allele is a major gene for CD tolerance, and a DNA marker distinguishing between I and Ic alleles, named the “Ic marker”, has been shown to be effective for the selection of CD-tolerant soybean plants ( Ohnishi et al 2011 ). Cold-induced seed cracking (SC) is a type of seed damage that is even more severe than CD ( Senda et al 2018 , Yamaguchi et al 2014 , 2015b ). In typical SC-affected seeds, which also exhibit the CD phenotype, the seed coat splits on the dorsal side, and the two inside cotyledons are exposed and separated ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a phytotron-based assay, we previously identified the cultivar Yukihomare (YH) and the breeding line Toiku 248 (T248) as susceptible and tolerant to SC, respectively, and detected two quantitative trait loci (QTLs) related to SC-tolerance, qCS8-1 and qCS11-1 , using recombinant inbred lines derived from a cross between T248 and YH ( Yamaguchi et al 2014 , 2015b ). We proposed the following model to explain the mechanism of SC in YH: under 21-day low-temperature treatment, PA accumulation expands to the dorsal side of the seed coat, and subsequent lignin deposition changes physical properties of the seed coat; as a result, a straight-line split occurs on the dorsal side of the seed coat at the full-sized seed stage, and SC takes place during seed maturation ( Senda et al 2018 ). In SC-tolerant T248, which possesses the IcIc genotype, PA accumulation is suppressed on the entire seed coat, even under low-temperature treatment, resulting in tolerance to SC ( Senda et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated average temperatures over a recent 10-year period in July, the period of sensitivity to chilling temperature, in Abashiri and Kamishihoro were 560 and 579°C, respectively. In the years of cold weather, cold-induced cracking seeds also appear in addition to CD in the Okhotsk area (Senda et al . 2018, Yamaguchi et al .…”
Section: Introductionmentioning
confidence: 99%